Case-Based Method for Enhancing Critical Thinking in English Debate Courses - Al Firdaus, Moch. Malik (Universitas Tidar, 2024)
This study investigates the challenges faced by students in expressing critical thinking and evaluates the implementation of the Case-Based Method in an English Debate and Critical Thinking (EDCT) course. Using a qualitative research design, data were collected from 35 undergraduate students through classroom observations, weekly reflections, and instructor interviews. The study identifies three primary challenges: a lack of understanding of debate fundamentals, insufficient critical thinking practice due to large class sizes, and limited knowledge of current issues, all of which hindered students’ ability to construct and articulate arguments effectively. To address these challenges, the study introduces the IDR (Introducing, Debating, Reviewing) framework. In the